Influence of atmosphere on high‐temperature oxidation of Fe‐Cr‐Si model alloy. Issue 8 (10th April 2019) - Issartel, Christophe; Buscail, Henri; Mathieu, Stéphane
Abstract: The aim of this study is to show the influence of the gaseous environment on the ferritic Fe‐Cr‐Si model alloy oxidation during 70 hrs, at 900 and 950°C. Two different atmospheres have been used, air or nitrogen containing 5 vol% hydrogen (N2 –5%H2 ). After air oxidation, a nonadherent chromia scale formed. In the N2 –5%H2 gaseous environment, it clearly appears that silicon segregation near the internal scale‐metal interface is favoured. In this low oxygen‐containing gas, adherent chromia, and silica scales have been formed. Silica subscale associated to an adherent chromia scale obtained in low‐oxygen conditions are a good protection barrier against carburisation. Abstract : This study shows the influence of N2 –5 vol% H2 on the ferritic Fe‐Cr‐Si oxidation during 70 hrs, at 900 and 950°C. In air, the obtained scale was chromia and was not adherent. In low‐oxygen atmosphere chromia and silica scales form and no spallation is observed. Low‐oxygen partial pressure causes certainly a change in the transport mechanism for oxide growth from predominantly cation to predominantly anion diffusion.